Treatment algorithms for high responders: What we can learn from randomized controlled trials, real-world data and models. (February 2023) - Drakopoulos, Panagiotis; Khalaf, Yakoub; Esteves, Sandro C.; Polyzos, Nikolaos P.; Sunkara, Sesh K.; Shapiro, Daniel; Rizk, Botros; Ye, Hong; Costello, Michael; Koloda, Yulia; Salle, Bruno; Lispi, Monica; et al.
Abstract: A high ovarian response to conventional ovarian stimulation (OS) is characterized by an increased number of follicles and/or oocytes compared with a normal response (10–15 oocytes retrieved). According to current definitions, a high response can be diagnosed before oocyte pick-up when >18–20 follicles ≥11–12 mm are observed on the day of ovulation triggering; high response can be diagnosed after oocyte pick-up when >18–20 oocytes have been retrieved. Women with a high response are also at high risk of early ovarian hyper-stimulation syndrome (OHSS)/or late OHSS after fresh embryo transfers. Women at risk of high response can be diagnosed before stimulation based on several indices, including ovarian reserve markers (anti-Müllerian hormone [AMH] and antral follicle count [AFC], with cutoff values indicative of a high response in patients with PCOS of >3.4 ng/mL for AMH and >24 for AFC). Owing to the high proportion of high responders who are at the risk of developing OHSS (up to 30%), this educational article provides a framework for the identification and management of patients who fall into this category. The risk of high response can be greatly reduced through appropriate management, such as individualized choice of the gonadotropin starting dose, dose adjustment based on hormonal and ultrasound monitoring during OS, the choice of down-regulation protocol and ovulation trigger, and the choice between fresh or elective frozen embryo transfer. Appropriate management strategies still need to be defined for women who are predicted to have a high response and those who have an unexpected high response after starting treatment. Highlights: Women with a high response to ovarian stimulation have an increased risk of OHSS. High response may be predicted before ovarian stimulation based on established indices. In some women, the high response to ovarian stimulation is unexpected. Clear guidelines on treatment strategies for high responders are needed and have been provided in this article. These should cover patient management before, during and after ovarian stimulation.